Transducer Electronic Data Sheets: Anywhere, Anytime, Anyway - Viegas, Vítor (2019)
Transducer electronic data sheets (TEDS) are a key element of smart transducers because they support core features such as plug and play, self-calibration, and self-diagnostics. The ISO/IEC/IEEE 21451-4 standard defines templates to describe the most common types of transducers and suggests the use of one-wire memories to store the corresponding data. In this paper we explore new ways to store and access TEDS tables, including near field communication (NFC) tags and QR codes. We also present a mobile TEDS parser, compatible with Android, that is capable of reading TEDS data from all supported mediums (one-wire memories, NFC tags, and QR codes) and decoding them as human-readable text. The idea is to make TEDS available in the easiest way possible. We also underline the need to extend the 21451-4 standard by adding support for frequency–time sensors. A new TEDS template is proposed, and filling examples are presented. The main novelties of the paper are (i) the proposal of new ways to store 21451-4 TEDS tables using NFC tags and QR codes; (ii) the release of new tools to access TEDS tables including a mobile parser; and (iii) the definition of a new TEDS template for frequency–time sensors.